2011
DOI: 10.1111/j.1532-5415.2011.03345.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D on Muscle Strength and Mobility in Older Women

Abstract: REFERENCES 1. Delbaere K, Close JCT, Heim J et al. A multifactorial approach to understanding fall risk in older people. J Am Geriatr Soc 2010;58:1679-1685. 2. Delbaere K, Close JCT, Brodaty H et al. Determinants of disparities between perceived and physiological risk of falling among elderly people: Cohort study. BMJ 2010;341:c4165. 3. Lord SR, Menz HB, Sherrington S. Home environment risk factors for falls in older people and the efficacy of home modifications. Age Ageing 2006; 35-S2:55-59. 4. Clemson L, Mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…weakness (82)(83)(84)(85)(86)(87). Moreover, serum vitamin D levels below 20 ng/mL (50 nmol/L) are associated with increased body sway and decreased muscle strength (15) and significant increased risk for falls (88).…”
Section: Manifestation Of Vitamin D Deficiencymentioning
confidence: 99%
“…weakness (82)(83)(84)(85)(86)(87). Moreover, serum vitamin D levels below 20 ng/mL (50 nmol/L) are associated with increased body sway and decreased muscle strength (15) and significant increased risk for falls (88).…”
Section: Manifestation Of Vitamin D Deficiencymentioning
confidence: 99%
“…An adequate and balanced diet is indispensable to maintain an adequate muscle function. An inverse relationship has been seen between muscle strength and circulating vitamin D levels, and the presence of vitamin D receptors in muscle and the positive action of vitamin D on muscle metabolism are known (85). Studies have shown that calcium and vitamin D supplementation reduces the risk of falls in the elderly, probably as the result of increased muscle strength and maintenance of neuromuscular coordination.…”
Section: Musculoskeletal Changesmentioning
confidence: 99%
“…To the Editor : Drs. Kaloostian and Shil 1 raise several points for discussion relating to our recent paper, 2 which included extra data from our original study 3 . They consider that data on the beneficial effects of vitamin D on lower limb function are well known and refer to a review that cited a previous epidemiological study as evidence for the effects of low serum 25‐hydroxyvitamin D (25(OH)D) on walking speed 4 .…”
mentioning
confidence: 99%
“…Drs. Kaloostian and Shil also suggest possible confounding of the study outcome due to poor renal function or hormone replacement therapy (HRT) 1 . These and other potential confounding factors were carefully taken into account in the study design.…”
mentioning
confidence: 99%